PERKIRAAN PADAT TEBAR OPTIMUM BERDASARKAN KEBUTUHAN OKSIGEN TERLARUT PADA IKAN KERAPU TIKUS (Epinephelus cromileptes) DAN KERAPU MACAN (Epinephelus fuscogutattus) - Arif Dwi Santoso; Wahyu Purwanta (Universitas Gadjah Mada, 2008)
The objective of this research was to find out the optimum stocking density of Grace Kelly grouper (Epinephelus cromileptes) and Tiger grouper (Epinephelus fuscogutattus) based on the dissolved oxygen budged.The experiment of fish respiration and general oceanographic surveys were conducted in aquaculture area of Hurun Bay, Lampung, in June 2003. The main equipment, namely transparant fish chamber that equipped with dissolved oxygen (DO), temperature sensor and a pump were constructed to measure the DO consumption of groupers. Environmental parameters of Hurun Bay estuary, such as DO, temperature, water-river supply, turbidity, salinity and water current were monitored at the site of 13.5 m3 floating net cage. The range and average of DO inside the cage was 3.68 – 6.76 (5.35) mg/L with water temperature 28.64 – 29.72 (29.09)0C, salinity 32.69 – 33.0 (32.94)o/oo and turbidity 0.27 – 13.62 (1,15) NTU, respectively. Inflow water rate of cage was 72 m3/hr and current velocity 2.3 - 5.1 cm/s. The respiration rate of juvenile and smaller were higher than adult fish. The exponential functions of optimum stocking density was found for E. cromileptes and E. fuscogutattus Y = 2806 X -0.8924 and Y = 1505.6 X -0.632 , respectively. There are two ways in order to increase stocking density, namely extention in area and increasing in volume of cage. On the base of DO budged, an estimation optimum stocking density for E. cromileptes was 134 ind/m3 for fish 50 g in average, 32 ind/m3 for fish 200 g and 8 ind/m3 for fish more than 1200 g. Meanwhile the optimum stocking density for E. fuscogutattus was 176 ind/m3 for fish 50 g in average, 63 ind/m3 for fish 200 g and 17 ind/m3 for fish more than 1200 g.